Tissue mechanics modulate PCNP expression in oral squamous cell carcinomas with different differentiation - Zhang, Leyang; Guo, Dingcheng; Shen, Junjie; Zheng, Yayuan; Zhai, Junkai; Li, Ruiping; He, Dengqi; Zhang, Baoping (Frontiers in Oncology, 2023)
Abstract Background: PEST-containing nuclear protein (PCNP), a novel zinc finger protein, participates in cell cycle regulation. Previous studies have confirmed that PCNP plays a role in mediating cellular development and invasion in a variety of cancer types. However, the relationship between PCNP expression and the occurrence and development of oral squamous cell carcinoma (OSCC) requires further exploration. In this study, we used biological atomic force microscopy to examine the histomorphological and mechanical properties of OSCC to explore the relationship between PCNP expression and differentiation of OSCC. Methods: Seventy-seven OSCC samples with varying degrees of differentiation were selected for hematoxylin and eosin staining, immunohistochemistry, and cellular mechanical measurement. The expression of PCNP and the mechanical properties such as stiffness and roughness of the tissue interface in OSCC samples were investigated. The Kaplan-Meier survival curve was utilized to assess the relationship of PCNP expression with patient survival. Results: The level of PCNP was significantly higher in well-differentiated OSCC than in moderately and poorly differentiated OSCC (P < 0.001). High expression of PCNP was specifically associated with higher tumor differentiation, lack of lymph node metastasis, and lower tumor node metastasis stage (all P < 0.05). Patients with high PCNP expression had a higher survival rate than those with low PCNP expression. The average variation of stiffness within a single tissue ranged from 347 kPa to 539 kPa. The mean surface roughness of highly, moderately, and poorly differentiated OSCC and paraneoplastic tissues were 795.53 ± 47.2 nm, 598.37 ± 45.76 nm, 410.16 ± 38.44 nm, and 1010.94 ± 119.07 nm, respectively. Pearson correlation coefficient demonstrated a positive correlation between PCNP expression and tissue stiffness of OSCC (R = 0.86, P < 0.001). Conclusion: The expression of PCNP was positively correlated with patient survival, tumor differentiation, and mechanical properties of tissue interfaces. PCNP is a potential biomarker for the early diagnosis and staging of OSCC. Furthermore, determination of the mechanical properties of the tissue interface could provide further useful information required for the detection and differentiation of OSCC.